GAMBARAN KESEHATAN LANJUT USIA DENGAN PARAMETER KADAR KOLESTEROL TOTAL KADAR GLUKOSA DARAH PUASA DAN KADAR ASAM URAT - Subroto, H.; Gunadi, J.W.; Jasaputra, D.K.; Tjokropranoto, R.; ,, Elizabeth; Indriani, J.; Siregar, E.H.D.; Octresna, N.; Kiswanto, A.D.M.; Tambatjong, G.H.K. (Buletin Udayana Mengabdi; Vol 23 No 5 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i05.p02, 2023)
The aging process in humans is a process experienced by everyone. The elderly population may experience several health problems such as diabetes, dyslipidemia, hyperuricemia, and hypertension. Some health parameters, especially for the elderly that need to be checked and controlled, include total cholesterol levels, fasting blood glucose levels, and uric acid levels, as well as blood pressure checks. The purpose of this community service activity is to assess the health of the elderly at Posbindu RW03 Pamoyanan Village, Cicendo District, Bandung, West Java with several examination parameters, namely total cholesterol levels, fasting blood glucose levels, and uric acid levels, as well as blood pressure checks. The results of the implementation of the activities are as follows: (1) normal cholesterol levels of 34.92%, and excess 65.08%, (2) normal fasting blood glucose levels of normal 74.6%, and those more than 126 mg / dL are 25.4%, (3) normal uric acid levels of 65.08%, and excess 34.92%, (4) Normal blood pressure amounted to 18 people (28.57%) and blood pressure of participants who were more than normal amounted to 45 people (71.43%). In conclusion, the elderly who were participants mostly had high cholesterol levels and increased blood pressure, while a small number of participants also experienced increased fasting blood glucose levels and increased uric acid levels. Keywords: Elderly, Cholesterol, GDP, Uric Acid, Blood Pressure.